The nutritional cacophony may be detrimental to your health - Fischler, C. (Progress in Nutrition, 2011)
Summary Contemporary societies live in a growing cacophony of health and nutrition news, advice, opinions, beliefs and recipes. This cacophony tends to raise the level of anxiety, yet there is no evidence that it can bring about significant health benefits. In the developed world, health policies have been governed more often than not by implicit assumptions which are discussed and criticized. The role of social and cultural dimensions in food and eating patterns is discussed and some novel directions for research are suggested. In particular, the paper hints at the need for comparative approaches between similarly developed countries and the possible positive role of social-cultural factors such as commensality or certain forms of it. Riassunto Le società contemporanee vivono in una cacofonia crescente di notizie, consigli, opinioni, credenze e ricette sulla salute e sulla nutrizione. Questa cacofonia tende ad aumentare il livello di ansia ma non vi è alcuna prova che possa portare significativi vantaggi per la salute. Nel mondo sviluppato le politiche sulla salute sono state regolate il più delle volte da assunzioni implicite che sono state discusse e criticate. In questo articolo è stato discusso il ruolo della dimensione sociale e culturale nel cibo e nelle abitudini alimentari suggerendo alcune nuove direzioni per la ricerca. In particolare il lavoro allude alla necessità di approcci comparativi tra i paesi similarmente sviluppati e il possibile ruolo positivo di fattori socio-culturali come la commensalità o alcune sue forme.